Motivasi Perawat Dalam Pelaksanaan Timbang Terima Pasien Sesuai SOP - Febrina, Wiwit (Universitas Fort De Kock Bukittinggi, 2021)
Backgroud: Nursing is one of a profession front for health workers in this effort to ensure the quality of health center in community. Handover is good quality health services to offer a service nursing on a patient care, To optimize the role and function of nurse especially function to independence nurse. This research aims to know the the relations motivation of a nurse with patient handover implementation as Standard Operational Procedure. Methods: The kind of research used is descriptive analytic with the approach cross sectional. A population that used is nurse who were 101 people from 101 a person who uses technique total of sampling. The analysis in use is analysis univariat and bivariat. Results: The results of the study was obtained between motivation meaningful a nurse with the implementation of these stations received patients (p = 0,000; OR = 9,389). Conclusion: Based on the research done can be concluded that there was a correlation meaningful of the incentives a nurse with the implementation of the weigh received patients appropriate with the Standard Operational Procedure. It was recommended to researchers , the hospital to continue to motivate nurse in the implementation of the weigh received patients appropriate with the Standard Operational Procedure. Keywords: Motivation, The Implementation of Handover